Acute Myocardial Infarction and its Association with ABO Blood Groups: A Study in Tertiary Care Hospital in Bangladesh - Islam, Lohani Md Tajul; Sultana, Sarjana; Islam, Md Ridwanul; Awal, Towhidur Rahman; Islam, Nayla; Kadir, ANM Monowarul; Mamun, Mohammad Al; Osmany, D M M F; Shameem, Md Kibria; Jobayer, Mohammad (University Heart Journal, 2025)
Background: Acute myocardial infarction (AMI), commonly known as a heart attack, remains a leading cause of morbidity and mortality worldwide. Among the various potential risk factors, the association between ABO blood groups and the incidence of acute myocardial infarction has garnered significant interest. This study aimed to assess the relationship between ABO blood group and acute myocardial infarction. Methods: This prospective observational study was conducted in the Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from March 2021 to July 2022. This study purposively enrolled 187 patients with acute myocardial infarction. After conducting thorough clinical examinations on all subjects, the information was documented in a data schedule. The data were then analyzed using SPSS version 23.0. Results: In this study, most participants were aged 46-65 years (51.3%) and from rural areas (57%). The male-female ratio was 2:1. The most prevalent ABO blood group was O+ve (30.5%), followed by B+ (27.8%), A+ (23.0%), and AB+ (12.8%). There was a significant correlation between ABO blood groups and gender of participants regarding AMI (p=0.002) but no significant correlation between ABO blood groups and or residency (p=0.179) regarding AMI. Conclusion: The rural male population aged 46-65 years is mostly prone to acute myocardial infarction. Among AMI patients, the most prevalent ABO blood group is O+ve, followed by B+ve. There is a significant correlation between ABO blood groups and gender of acute myocardial infarction patients. University Heart Journal 2024; 20(1): 18-21